THE INFLUENCE OF WORK CLIMATE, INTERPERSONAL COMMUNICATION, AND MANAGERIAL SUPPORT ON TEACHER LOYALTY IN STATE ISLAMIC JUNIOR HIGH SCHOOLS OF TANGERANG REGENCY - Dedi Herawadi; Naf’an Tarihoran; Eneng Muslihah (International Journal of Education and Social Science Studies, 2025)
This study aims to analyze the influence of work climate, interpersonal communication, and managerial support on teacher loyalty in eight State Islamic Junior High Schools in Tangerang Regency. The research is grounded in the importance of establishing a supportive work environment, effective communication, and empathetic leadership as strategic elements in strengthening teacher loyalty, which plays a crucial role in improving educational quality. A quantitative approach was employed using a survey method. Data were collected through questionnaires distributed to 120 permanent and non-civil servant teachers. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 26 to examine both partial and simultaneous effects of the independent variables on teacher loyalty. The findings indicate that work climate, interpersonal communication, and managerial support each have a positive and significant effect—both individually and collectively—on teacher loyalty. A conducive work environment fosters a sense of security and comfort, enabling professionals to carry out their duties effectively. Effective interpersonal communication strengthens harmonious working relationships, while strong managerial support fosters trust and appreciation for teachers’ contributions. Conclusions: The study highlights the need to enhance the organizational capacities of school leaders in creating a work environment that promotes long-term teacher loyalty. These findings offer valuable insights for educational management in religious-based schools that aim to retain and empower their teaching staff.